Rapid synthesis of titanium(IV)‐immobilized magnetic mesoporous silica nanoparticles for endogenous phosphopeptides enrichment. Issue 8 (17th March 2017) - Yao, Jizong; Sun, Nianrong; Wang, Jiawen; Xie, Yiqin; Deng, Chunhui; Zhang, Xiangmin
Abstract : The MALDI‐TOF MS has already been a main platform for phosphoproteome analysis. However, there are some weaknesses in direct analysis of endogenous phosphopeptides by MALDI‐TOF MS because of the serious suppression effect and poor ionization efficiency, which is brought by the excess of nonphosphopeptides and protein. It is essential to enrich endogenous phosphopeptides from complex biosamples efficiently prior to MALDI‐TOF MS analysis. Herein, we present a time‐saving and detailed protocol for the synthesis of titanium(iv)‐immobilized magnetic mesoporous silica nanoparticles (denoted as Fe3 O4 @mSiO2 ‐Ti 4+ ), the subsequent enrichment process, and MALDI‐TOF MS analysis. We tested the LOD, size‐exclusive effect, reproducibility, and stability of Fe3 O4 @mSiO2 ‐Ti 4+ nanoparticles. Furthermore, the ability of this protocol for identifying endogenous phosphopeptides in healthy human serum and saliva was investigated.